Gastric Neuroendocrine Tumors With Parietal Cell Atrophy in a Long-term Carcinogenicity Study in Rats. (June 2022) - Shirai, Norimitsu; Choudhary, Shambhunath; Houle, Christopher
Malignant neuroendocrine tumors were diagnosed in the stomach of two out of sixty female Sprague-Dawley rats treated for 89 weeks with a high dose of a novel, small molecule, cannabinoid-1 antagonist. The tumors were associated with parietal cell atrophy accompanied by foveolar hyperplasia of the glandular stomach mucosa. Parietal cell atrophy/foveolar hyperplasia was considered test article related at the high dose, given the higher incidence and severity relative to untreated controls, although the precise mechanism of the parietal cell atrophy was undetermined. Spontaneous gastric neuroendocrine tumors are very rare in rats, and the current cases were considered secondary to parietal cell atrophy causing reduced gastric acid secretion and subsequent overstimulation of gastrin release through a feedback loop.